On the orbital inclination evolution of the current large NEOs - de Araujo, Rosana A. N. [UNESP]; Liberato, Luana [UNESP]; Winter, Othon C. [UNESP] (Springer Nature, 2023)
This work aims to discuss the temporal evolution of the current large NEOs’ orbital inclination. We applied a numerical integration method to solve the N-body gravitational problem. We used Mercury’s hybrid symplectic/Bulirsch-Stoer algorithm to perform the integrations, covering a period of 100 million years, for a sample of 985 current large NEOs, the Sun, and the eight planets of the solar system. We found that the NEOs with initially low inclinations tend to significantly and rapidly increase their orbital inclinations. We also identified an intermediate range of inclinations between 20 and 60 ∘ where the objects tend to be less perturbed, which is favourable for the long-lived NEOs. We also found that the NEOs with very high initial inclinations are lost more quickly unless they are brought into the intermediate range by decreasing their orbital inclination. The results of this study provide new insights into the current distribution of NEOs orbital inclinations. Overall, we have shown that the evolution through the terrestrial planets region effectively changes the NEOs’ orbital inclination, often through a gradual accumulation. The changes result from a combination of typical perturbations in this region and may impact various aspects of the minor bodies’ orbital evolution, such as their lifespans and fates.